Keterbatasan Inovasi Produk dalam Perbankan Syariah Indonesia: Analisis Struktural atas Hambatan Regulatif, Kelembagaan, dan Teknologi - Fadillah Muawana; Mellyan Mellyan; Yoni Hendrawan (Universitas Hamzanwadi, 2025)
This study aims to critically examine the structural barriers limiting product innovation in Indonesia’s Islamic banking sector. Employing a qualitative method through a literature-based approach, this study analyzes academic publications, regulatory documents, and industry reports related to innovation in Islamic finance. The findings identify four major categories of challenges: regulatory complexity and Shariah compliance, limited human capital capabilities, slow digital transformation, and weak collaboration among academics, regulators, and industry actors. These factors interact and form a systemic structural hindrance to the innovation process. The study recommends regulatory reform grounded in maqashid al-shari’ah, capacity-building of human resources, digital adoption aligned with Islamic values, and the development of a sustainable, collaborative ecosystem. This research contributes to the discourse on strengthening Islamic financial innovation through an integrative and context-responsive framework